Activation of Serotonin 5-HT7 Receptors Modulates Hippocampal Synaptic Plasticity by Stimulation of Adenylate Cyclases and Rescues Learning and Behavior in a Mouse Model of Fragile X Syndrome - Costa, Lara; Sardone, Lara Maria; Bonaccorso, Carmela Maria; D’Antoni, Simona; Spatuzza, Michela; Gulisano, Walter; Tropea, Maria Rosaria; Puzzo, Daniela; Leopoldo, Marcello; Lacivita, Enza; Catania, Maria Vincenza; Ciranna, Lucia (Frontiers in Molecular Neuroscience, 2018)
We have previously demonstrated that activation of 5-HT7 receptors (5-HT7R) for serotonin reverses metabotropic glutamate receptor-mediated long term depression (mGluR-LTD) in the hippocampus of wild-type (WT) and Fmr1 Knockout (KO) mice, a model of Fragile X Syndrome (FXS). Here, we have investigated possible underlying 5-HT7R-activated intracellular action mechanisms. Furthermore, we have tested whether in vivo administration of LP-211, a selective 5-HT7R agonist, can rescue learning and behavior in Fmr1 KO mice. Using patch clamp on hippocampal slices, we observed that mGluR-LTD in WT slices was enhanced by SQ 22536 and was abolished by forskolin, respectively blocking and stimulating adenylate cyclase. In Fmr1 KO slices, mGluR-LTD was exaggerated with respect to WT and was not further enhanced by adenylate cyclase blockade, suggesting that in Fmr1 KO neurons low basal cAMP levels may contribute to enhanced mGluR-LTD. Conversely, application of forskolin completely reversed mGluR-LTD in Fmr1 KO slices, as observed in WT. Application of LP-211 reversed mGluR-LTD in WT and corrected exaggerated mGluR-LTD in Fmr1 KO, confirming our previous results. 5-HT7R-mediated reversal of mGluR-LTD was abolished by blockade of either adenylate cyclase or protein kinase A (PKA). Exposure of hippocampal slices to LP-211 increased phosphorylation of extracellular signal regulated kinase (ERK), an intracellular effector involved in mGluR-LTD and known to be dysregulated in the brain of Fmr1 KO mice. Finally, LP-211 was administered to WT and Fmr1 KO mice and effects on learning and stereotyped behavior were evaluated using the novel object recognition (NOR) test and the marble burying test. Acute in vivo administration of LP-211 improved NOR performance in WT and Fmr1 KO mice and reduced stereotyped behavior in Fmr1 KO mice. Our results suggest that hippocampal neurons from Fmr1 KO mice have low intracellular cAMP levels and this condition is associated with exaggerated mGluR-LTD. Furthermore, we show that a 5-HT7R agonist reverses mGluR-LTD by activation of the cAMP/PKA intracellular pathway and concurrently stimulates ERK. Consistently, a systemic administration of a 5-HT7R agonist to Fmr1 KO mice corrected learning deficits and repetitive behavior. We suggest that selective 5-HT7R agonists might become novel pharmacological tools for FXS therapy.